Postmortem Interval Influences α-Synuclein Expression in Parkinson Disease Brain - Alexandra Dumitriu; Carlee Moser; Tiffany C. Hadzi; Sally L. Williamson; Christopher D. Pacheco; Audrey E. Hendricks; Jeanne C. Latourelle; Jemma B. Wilk; Anita L. DeStefano; Richard H. Myers (Parkinson's Disease)
Duplications and triplications of the α-synuclein (SNCA) gene increase risk for PD, suggesting increased expression levels of the gene to be associated with increased PD risk. However, past SNCA expression studies in brain tissue report inconsistent results. We examined expression of the full-length SNCA transcript (140 amino acid protein isoform), as well as total SNCA mRNA levels in 165 frontal cortex samples (101 PD, 64 control) using quantitative real-time polymerase chain reaction. Additionally, we evaluated the relationship of eight SNPs in both 5′ and 3′ regions of SNCA with the gene expression levels. The association between postmortem interval (PMI) and SNCA expression was different for PD and control samples: SNCA expression decreased with increasing PMI in cases, while staying relatively constant in controls. For short PMI, SNCA expression was increased in PD relative to control samples, whereas for long PMI, SNCA expression in PD was decreased relative to control samples.